TEKNIK VOKAL DALAM PENYAJIAN TEKSTUR POLIFONI PADA MEDLEY NYANYIAN NUSANTARA OLEH ANDALASWARA CHOIR - Intan Putri Pramanandi; Maestro, Esy (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the application of vocal techniques in the presentation of polyphonic texture in the Medley Nyanyian Nusantara performed by Andalaswara Choir. This research employed a qualitative descriptive approach with data collected through observation, interviews, and documentation. The results show that the presentation of the work requires mature mastery of vocal techniques, particularly breathing, resonance, articulation, and intonation. These techniques play an important role in shaping choral sonority that is balanced, resonant, and blended across all voice parts. In addition, the complexity of polyphonic texture demands consistency of vocal technique from soprano, alto, tenor, and bass sections, especially when combined with choreography and traditional costumes. With proper vocal technique management and intensive rehearsal, Andalaswara Choir was able to present the Medley Nyanyian Nusantara optimally and harmoniously.